2017
DOI: 10.1007/s13524-017-0590-2
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Life Satisfaction in Rural Ethiopia

Abstract: There is a growing number of studies focusing on the role of fertility in subjective well-being in developed countries while developing countries have been rarely taken into account. We investigate the empirical relationship between fertility and life satisfaction in rural Ethiopia, the largest landlocked country in Africa providing the unique opportunity of panel data availability. Our results suggest that older men benefit the most in terms of life satisfaction from the investment in children, the latter bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 69 publications
5
20
2
Order By: Relevance
“…Among older Malawians, having more (adult) children is associated with better outcomes across all three psychological measures for older women and greater life satisfaction for older men. These findings differ from the study in rural Ethiopia which found that only older men who had more children experienced heightened life satisfaction (Conzo, Fuochi and Mencarini 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Among older Malawians, having more (adult) children is associated with better outcomes across all three psychological measures for older women and greater life satisfaction for older men. These findings differ from the study in rural Ethiopia which found that only older men who had more children experienced heightened life satisfaction (Conzo, Fuochi and Mencarini 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the value and centrality of children in the lives of Malawians (Dyer 2007), the number of children is not correlated with any measure of men's or women's psychological wellbeing during their reproductive years. This is consistent with our expectations and findings from rural Ethiopia (Conzo, Fuochi and Mencarini 2017), but differs from crosssectional analyses of low-income countries showing a strong negative association between both negative emotions (Deaton and Stone 2014) and life satisfaction (Margolis and Myrskylä 2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Children sex composition may also affect the level of one's happiness [14]. In this study, children's sex composition has a significant effect on men's happiness.…”
Section: Resultsmentioning
confidence: 58%